2011
DOI: 10.1103/physreve.83.041112
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein condensation and a two-dimensional walk model

Abstract: We introduce a two-dimensional walk model in which a random walker can only move on the first quarter of a two-dimensional plane. We calculate the partition function of this walk model using a transfer matrix method and show that the model undergoes a phase-transition. Surprisingly the partition function of this two-dimensional walk model is exactly equal to that of a driven-diffusive system defined on a discrete lattice with periodic boundary conditions in which a phase transition occurs from a high-density t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Comparing this partition function with that of the drivendiffusive model we have shown that these two model are equivalent. It should be noted that the walk model introduced in [11] and the one introduced in present work can be mapped onto zero-range process.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Comparing this partition function with that of the drivendiffusive model we have shown that these two model are equivalent. It should be noted that the walk model introduced in [11] and the one introduced in present work can be mapped onto zero-range process.…”
Section: Discussionmentioning
confidence: 98%
“…The density profile of the model is calculated exactly and the spatial correlations of the model are obtained in terms of 1-point correlation function. We have introduced a two-dimensional walk model in which the random walker, in contrast with the lattice path introduced in [11], can start from any height upper than the origin and that the end point of the lattice path can be at any height upper than the start point. This type of lattice path is introduced in [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We will show that our new family of exactly solvable systems can be mapped onto a ZRP. Similar systems have already been studied in related literature [4,18,19]. We start with a disordered exclusion process defined on a one-dimensional lattice of finite size with periodic boundary conditions.…”
Section: Introductionsmentioning
confidence: 99%